Gas-Assisted Heating Technology for High Aspect Ratio Microstructure Injection Molding. (25th September 2013) - Chen, Shia-Chung; Lin, Chen-Yang; Chang, Jen-An; Minh, Pham Son
Abstract : A hot gas is used for heating the cavity surface of a mold. Different mold gap sizes were designed. The mold surface temperature was heated to above the glass transition temperature of the plastic material, and the mold then closed for melt filling. The cavity surface can be heated to 130°C to assist the melt filling of the microfeatures. Results show that hot gas heating can improve the filling process and achieve 91% of the high aspect ratio microgrooves (about 640.38  μ m of the maximum of 700  μ m). The mold gap size strongly affects the heating speed and heating uniformity. Without surface preheating, the center rib is the highest. When the heating target temperature is 90°C or 100°C, the three microribs have a good uniformity of height. However, when the target temperature exceeds 100°C, the left side rib is higher than the other ribs.